An elevated parametric thyroid feedback quantile-based index is associated with atrial fibrillation - Alonso-Ventura, Vanesa; Campos-Magallon, Patricia; Moreno-Franco, Belen; Calmarza, Pilar; Calvo-Gracia, Fernando; Lou-Bonafonte, Jose Manuel; de Diego-Garcia, Patricia; Casasnovas, Jose Antonio; Marco-Benedi, Victoria; Civeira, Fernando; Laclaustra, Martin (Frontiers in Endocrinology, 2023)
Introduction Atrial fibrillation is associated with hyperthyroidism. Within the euthyroid range, it is also associated with high thyroxine (fT4), but not with thyrotropin (TSH). We aim to describe differences in thyroid regulation, measured by the Parametric Thyroid Feedback Quantile-Based Index (PTFQI), between patients with atrial fibrillation and the general population. Materials and methods Thyroid parameters (PTFQI, TSH, and fT4) of a sample of 84 euthyroid subjects with atrial fibrillation (cases) were compared to a reference sample of euthyroid healthcare patients (controls). We calculated age and sex adjusted ORs for atrial fibrillation across tertiles of these parameters. Also, within cases, we studied thyroid parameters association with clinical characteristics of the atrial fibrillation. Results After adjusting for age and sex, fT4 and PTFQI were higher in subjects with atrial fibrillation when compared to the general sample (p<0.01 and p=0.01, respectively). Atrial fibrillation ORs of the third versus the first PTFQI tertile was 1.88(95%CI 1.07,3.42), and there was a gradient across tertiles (p trend=0.02). Among atrial fibrillation patients, we observed that higher PTFQI was associated with sleep apnea/hypopnea syndrome (OSAS) (p=0.03), higher fT4 was associated with the presence of an arrhythmogenic trigger (p=0.02) and with heart failure (p<0.01), and higher TSH was also associated with OSAS (p<0.01). Conclusions Euthyroid subjects with atrial fibrillation have an elevation of the pituitary TSH-inhibition threshold, measured by PTFQI, with respect to the general population. Within atrial fibrillation patients, high PTFQI was associated with OSAS, and high fT4 with heart failure. These results hint of the existence of a relationship between thyroid regulation and atrial fibrillation.